Enhancing Performance of Composite-Based Triboelectric Nanogenerators Through Laser Surface Patterning and Graphite Coating for Sustainable Energy Solutions - Narong Amorntep; Apirat Siritaratiwat; Chavis Srichan; Saichon Sriphan; Thalerngsak Wiangwiset; Atthaporn Ariyarit; Wisut Supasai; Nuttapong Bootthanu; Sorawit Narkglom; Naratip Vittayakorn; Chayada Surawanitkun (Energies)
The performance of composite-based triboelectric nanogenerators (C–TENGs) was significantly enhanced through laser surface patterning and graphite coating. The laser etching process produced accurate and consistent patterns, increasing surface area and improving charge accumulation. SEM imagery confirmed the structural differences and enhanced surface properties of the laser-etched C–TENGs. Graphite fibers further augmented the contact surface area, enhancing charge accumulation and diffusion. Experimental results demonstrated that the optimized C–TENGs, especially those with line patterns and graphite coating, achieved a maximal 98.87 V open-circuit voltage (VOC) and a 0.10 µA/cm2 short-circuit current density (JSC) under a 20 N external force. Environmental tests revealed a slight decrease in performance with increased humidity, while long-term stability tests indicated consistent performance over three weeks. Practical application tests showed the potential of C–TENGs integrated into wearable devices, generating sufficient energy for low-power applications, thereby highlighting the promise of these devices for sustainable energy solutions.